FAUNA DO SOLO EM DIFERENTES SISTEMAS DE PRODUÇÃO NO CERRADO, MS - MATEUS, Yasmin Hikari Ueno; PERES, Nathália Dias; SCHNECKEMBERG, Luiz Fernando López; SCHIAVO, Jolimar Antonio (ANAIS DO ENIC, 2026)
.